Rectal stenosis due to solitary pelvic recurrence of hilar cholangiocarcinoma. Issue 5 (16th May 2020) - Shioi, Ikuma; Yamaoka, Yusuke; Shiomi, Akio; Kagawa, Hiroyasu; Hino, Hitoshi; Manabe, Shoichi; Aizawa, Daisuke
Abstract: An 85‐year‐old woman was admitted to a hospital with abdominal pain. Five years prior to admission, she had a history of hilar cholangiocarcinoma of pStage IIIC. Contrast‐enhanced computed tomography showed a mass between the rectum and uterus as well as bowel obstruction due to the lesion. Colonoscopy showed severe stenosis at the lower rectum and elevation of the submucosal layer with linear erosion. Rectal cancer was suspected, and pelvic recurrence of hilar cholangiocarcinoma or endometrial carcinoma infiltrating the rectum was considered as differential diagnosis. She underwent robot‐assisted low anterior resection combined with partial resection of the uterus. The immunohistopathological findings of the resected specimen favored a diagnosis of metastasis of cholangiocarcinoma, rather than primary rectal cancer or endometrial carcinoma. There were no signs of recurrence after 10 months of follow‐up. Hilar cholangiocarcinoma is a disease with poor prognosis. Recurrence is frequently experienced even after curative resection. Patients with recurrence are rarely candidates for re‐resection. However, better prognosis is reported for those with complete resection. Abstract : Hilar cholangiocarcinoma is a disease with poor prognosis; recurrences are frequently experienced even after curative resection. However, very few reports focus on resection of the recurrence site. We herein report a unique case of rectal stenosis due to solitary pelvic recurrence of cholangiocarcinoma which was successfully resected.